The Comparison of Education System in Australia and Indonesia - Marmoah, Sri; Roslan, Roslinawati; Chaeroh, Miratu; Elita, Mutiara Dana; Fauziah, Muna (Jurnal Pendidikan Indonesia, 2021)
The education system is a method for directing the educational process. All aspects of learning must be regulated by the educational system. Because each country has a unique system, it is necessary to compare the education system in Indonesia to that of other countries in order to assess and evaluate it. This paper aims to explain and analyze differences in educational systems; and comparing the basic education curricula in Indonesia and Australia. This research is conceptual. Data collection methods are books, the internet, and journals. The study analysis was carried out by collecting and analyzing information about the education system in Indonesia and Australia. The results of the study show that: (1) Australia requires children to study for 10 years, while in Indonesia for 12 years, Australia holds a NAPLAN test and Indonesia holds a NE, and teacher qualifications must be undergraduate in Australia and Indonesia; (2) differences in the education system, among others, the level of material difficulty, assessment, rewards, learning atmosphere, teaching staff, education staff, and religious subjects; and (3) the curriculum in Indonesia has a relationship between education, customs, arts, and religions, meanwhile, the Australian curriculum is designed to support students to be successful, active, well-off and knowledgeable.